2021
DOI: 10.1186/s12913-021-06828-z
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of eye bank versus surgeon prepared endothelial grafts

Abstract: Background Selective lamellar corneal transplantation (keratoplasty) has overtaken full thickness penetrating keratoplasty as the graft choice for endothelial failure. Even more recently eye bank prepared tissues are becoming increasing popular as a way to reduce the risks of tissue loss and stress during endothelial keratoplasty preparation in the surgical theatre. This study compares costs between surgeon and eye bank prepared tissues for Descemet’s stripping automated endothelial keratoplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…15 In our setting, we have found that as pl-DMEK tissues save time in the surgery, both in terms of graft preparation and the graft opening time in the anterior chamber, it does have an impact on the overall costs. 16 A similar impact 17 has been reported in a different setting, with endo-out technique. In addition to the accountable factors as listed above, the pros in terms of reduced surgical stress and tissue wastage, less surgical postponements or cancellations due to tissue wastage leading to patient distress and, reducing graft preparation stress cannot be neglected.…”
Section: Discussionsupporting
confidence: 63%
“…15 In our setting, we have found that as pl-DMEK tissues save time in the surgery, both in terms of graft preparation and the graft opening time in the anterior chamber, it does have an impact on the overall costs. 16 A similar impact 17 has been reported in a different setting, with endo-out technique. In addition to the accountable factors as listed above, the pros in terms of reduced surgical stress and tissue wastage, less surgical postponements or cancellations due to tissue wastage leading to patient distress and, reducing graft preparation stress cannot be neglected.…”
Section: Discussionsupporting
confidence: 63%
“…However, another study reported that eye bank-prepared DMEK grafts incur relatively higher surgical expenses compared with surgeon-prepared DMEKs. 34 More multicenter studies with regard to cost analysis are required to further confirm the cost effectiveness of preloaded DMEK.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the eye banks initiated the provision of prestripping followed by preloaded DMEK grafts in response to reducing time, stress, costs, and efforts in the surgical theater. 28 In 2018, Busin et al 13 highlighted several advantages of preloaded DMEK grafts with endothelium trifolded inward that included 29.5% ECL with 19.6% rebubbling rates. In a similar study, Price et al 29 reported 28% ECL and 10% rebubbling with the endo-in format.…”
Section: Discussionmentioning
confidence: 99%